Combination of Progressive Muscle Relaxation (PMR) and Positive Affirmation on Mental Health Disorders in Pregnant Women - Pusporini, Dian Purwohadi; Sumarni, Sri; Latifah, Leny (Sarana Ilmu Indonesia (salnesia), 2025)
Pregnancy carried significant risks for women's mental health, leading to drastic changes at the social, biological, and psychological levels of expectant mothers. This study aimed to determine the effect of a combination of Progressive Muscle Relaxation (PMR) and positive affirmations on mental health disorders in pregnant women. This research was a true experimental study with a pretest-posttest control group design. The sampling technique used was Randomized Allocation based on inclusion criteria. A total of 40 participants were involved, with 20 in the intervention group and 20 in the control group. The intervention group received a combination of PMR and positive affirmations three times a week, once daily, for a total of 6 sessions over 14 days. Data were collected using the SRQ-20 questionnaire. The Wilcoxon test was used to analyze within-group changes, and the Mann-Whitney test was applied to assess differences between groups. The average mental health score before the intervention was 6,05, which decreased to 3,85 after the intervention. The p-value before and after the combination therapy was < 0,05. It was concluded that the combination of PMR and positive affirmations effectively reduced mental health disorders in pregnant women.